Cover crops and no-till effects on physical fractions of soil organic matter - Nascente, Adriano Stephan; Li, Yuncong C.; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier, 2013)
Physical fractions (free light fraction, intra-aggregate light fraction and heavy fraction) of soil organic matter (SOM) are good indicators of soil quality for sustainable land use. The objective of this study was to evaluate the effect of cover crops on total organic carbon (TOC) and physical fractions of soil organic matter in soil under a no-tillage system (NTS) and a conventional tillage system (CTS, one plowing and two disking). A three-year field experiment was carried out as a cover crop-rice (Oryza sativa)-cover crop-rice rotation. Treatments included cover crops (Panicum maximum, Brachiaria ruziziensis, Brachiaria brizantha, and pearl millet (Pennisetum glaucum), fallow, till or no till. The SOM was physically fractionated in free light fraction (FLF), intra-aggregates light fraction (IALF) and heavy fraction (HF). The levels of C in whole soil were also evaluated, as well as C in the light fractions (FLF+IALF) and in the HF. Results indicated that concentrations of C in the FLF and IALF in surface soils (0-0.05m) were much higher (10.8 and 1.95gkg-1, respectively) than that in the 0.05-0.1m soil depth (7.68 and 1.54gkg-1, respectively) and in the 0.1-0.2m soil depth (4.98 and 1.24gkg-1, respectively). The NTS resulted in higher levels of FLF (12.2gkg-1) and IALF (2.19gkg-1) than with CTS (1.37-7.30gkg-1). Millet had the highest C (19.5gkg-1) and N (1.1gkg-1) concentrations in soil. There was an accumulation of TOC and total N in the surface soil with cover crops, and concentrations of TOC were higher in the HF (79.0%) than in the light fractions (21.0%). Although SOM changed little during the two years of this experiment, the various C fractions were significantly affected by the tillage treatments. We conclude that SOM physical fractionation allowed seeing significant differences caused by the soil management in the organic matter dynamics in a short period of time. © 2013 Elsevier B.V.
Keywords: Brachiaria brizantha; Brachiaria ruziziensis; Millet; Panicum maximum; Soil management; Aggregates; Agricultural machinery; Agronomy; Biogeochemistry; Biological materials; Crops; Cultivation; Organic compounds; Plants (botany); Soils; Soil pollution; conservation tillage; cover crop; fallow; grass; land use change; millet; plowing; rice; soil aggregate; soil depth; soil management; soil organic matter; soil quality; soil surface; sustainability; total organic carbon; zero tillage